Food responsiveness, addiction, and hyperphagia in Prader-Willi syndrome: a cross-sectional study of 210 Chinese patients - Hu, Chen-Xi; Xia, Fang-ling; Qin, Yi-Fang; Chao, Yun-Qi; Ruan, Yu-Lu; Li, Jing-Wen; Dong, Guan-Ping; Zou, Chao-Chun (Frontiers in Endocrinology, 2025)
ObjectivePrader–Willi syndrome (PWS) is the most common genetic syndromic obesity, characterized primarily by hyperphagia. It was described as excessive appetite, defective satiety, and obsession with food. However, the underlying mechanisms of hyperphagia in PWS remain obscure. This study aimed to determine the eating behavior patterns and food addiction tendencies in patients with PWS.Methods210 patients with PWS from 26 provinces in China were enrolled in this study. The translated Children’s Eating Behavior Questionnaire and modified Yale Food Addiction Scale for Children 2.0 were adopted for evaluation.ResultsThis study revealed that (i) In patients with PWS, the eating behavior patterns are abnormal and the risk of food addiction is high. (ii) Patients with higher food responsiveness (FR) have a higher risk of food addiction; (iii) Scores of food responsiveness, enjoyment of food, satiety response, and food addiction have already changed even before the onset of overweight or obesity. (iv) Growth hormone (GH) therapy is an independent factor influencing weight, with continuous treatment being beneficial for weight maintenance and earlier treatment being more advantageous. (v) FR is another key factor affecting body weight. Unfortunately, GH therapy does not improve food responsiveness.ConclusionsThis study indicates that GH treatment and FR are significant factors influencing hyperphagia and body weight in patients with PWS. Early involvement of psychotherapeutic interventions may help patients better manage hyperphagia-related behaviors and subsequent weight gain.